Case report on migrated foreign body of prevertebral space removed by lateral pharyngotomy approach - Lyngdoh, Nicola C.; Mariyapragasam M., Vanathu; Kalpana Devi, Thongam; Hynniewta, Ladeiti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Foreign bodies in the upper aerodigestive tract are common; fish bones form 85% of those foreign bodies, which commonly impacted in the palatine tonsils, the base of the tongue or at the level of the cricopharyngeal sphincter, cervical oesophagus. Rarely, they may migrate extraluminally. Here, we are reporting a case of an ingested fishbone that had migrated to the prevertebral space, which needed a lateral pharyngotomy approach for removal.